Infection Control in Healthcare Settings Challenges and Solutions for Improved Care Quality: A Systematic Review - Dh Alotaibi, Fawaz Mohammed; Mohammed Alfaifi, Khairiah Yahya Bin; Farhan Almalki, Abdullah Yahya; Ali Alshehri, Awadh Mohammed; Alyahya, Naif Fahad Nasser; Althobaiti, Wael Faisal Awwadh; Ahmed Alharthi, Yasir Atiah Bin; Obaidallah Alharbi, Mohammad Saud; Almutairi, Wael Salem Awadh (Journal of Neonatal Surgery, 2025)
Background: Healthcare-associated infections (HAIs) are a significant global challenge affecting morbidity, mortality and healthcare costs. Effective infection prevention and control (IPC) programs are essential. The healthcare system in Saudi Arabia is rapidly changing and has specific challenges related to the context of mass gathering (Hajj/Umrah) and high dependency on expat healthcare workers. Objective: This study aims to assess barriers that inhibit effective infection prevention and control (IPC) in order to better understand; the issue of infection prevention and control in kingdom and the impact of IPC on culturally appropriate practices in the provision of care, which may lead to HAI and other adverse outcomes. Methods: This present study follows a systematic review method (e.g., search strategy, databases included, inclusion/exclusion criteria, quality assessment tool like PRISMA. Focus on mostly original research (qualitative and quantitative) and review articles published on topic in the context of Saudi Arabia. Conclusion: Saudi Arabia has demonstrated its ability to enact a national effort of high significance (e.g. the CLABSI reduction campaign and ASPs) at the national level, but sustaining these advances and achieving world-class HAI rates will depend on continuing to address its existing substantial gaps: optimizing the IPC workforce and addressing compliance gaps among front-line healthcare workers..